DZNep attenuates allergic airway inflammation in an ovalbumin-induced murine model. (March 2021) - Li, Hang; Li, Jian; Lu, Tong; Chen, Dehua; Xu, Rui; Sun, Wei; Luo, Xi; Li, Huabin; Ma, Renqiang; Wen, Weiping
Highlights: EZH2 tended to be overexpressed in the airway tissues of OVA-sensitized BALB/c mice. Indirect inhibition of EZH2 using DZNep ameliorated the allergic airway inflammation. Our research showed a new view of epigenetic modulation in the development of allergic airway inflammation. Abstract: Background: Growing evidence shows that enhancer of zeste homolog 2 (EZH2) plays a role in various physiological functions and cancer pathogenesis. However, its contribution to allergic diseases remains controversial. We sought to investigate the role of EZH2 in the pathogenesis of allergic airway inflammation. Methods: 3-Deazaneplanocin A (DZNep), an indirect inhibitor of EZH2, was administered via intraperitoneal injection in an ovalbumin (OVA)-induced murine model of allergic airway inflammation. The expression of EZH2 in the allergic airway tissues was examined by immunohistochemistry (IHC) and western blot. The inflammatory cell infiltration and the goblet cell hyperplasia in the murine nose and lung were detected by hematoxylin and eosin (H&E) staining and periodic acid-Schiff (PAS) staining. Levels of cytokines, including IL-4, IFN-γ, IL-6, and IL-10, were evaluated in the bronchoalveolar lavage fluid (BALF) using Enzyme-linked immune sorbent assay (ELISA). Results: EZH2 expression was inhibited by DZNep treatment (P < 0.05). The administration of DZNep significantly inhibited the inflammatory cell infiltration (P < 0.0001) and goblet cell hyperplasia (P < 0.001). Moreover, it suppressed the secretion of IL-4 (P < 0.0001) and IL-6 (P < 0.01) in the BALF. Conclusions: Our findings demonstrate that DZNep attenuates allergic airway inflammation and could be a new therapeutic option for allergic rhinitis and asthma.